POTENSI DAN STRATEGI PENINGKATAN KUALITAS SDM BUMDES BERBASIS KOMPETENSI ERA INDUSTRI 5.0 - Djadji, Osfred Umbu; Adindarena, Vindya Donna (Publik: Jurnal Manajemen Sumber Daya Manusia, Administrasi dan Pelayanan Publik, 2025)
This study aims to identify potential, internal and external factors and formulate strategies to improve the quality of BUMDes human resources in the Industrial Era 5.0. Data were collected through observation, in-depth interviews and focus group discussions and analyzed qualitatively. This study concludes that there are 6 potential aspects that influence the improvement of the quality of human resources in the Industrial Era 5.0 such as work background, experience, knowledge, skills, attitudes and partner relations. In addition, internal factors that influence are knowledge, skills, attitudes, experience, HR development guidelines, partner relations, performance, collaboration, facilities and infrastructure and authority. While external factors are the development of science and technology, demographic changes and work patterns, competitive, improving performance and knowledge, skills and attitudes, changes in HR development methods, creativity and innovation, improving partner relations, use of IT, budget constraints, job transitions, lack of collaboration and the presence of competitors. The results of the strategy formulation are optimization of IT-based HR performance, development of a performance assessment system based on achievement and IT, cooperation with other business partners, product development, recruitment of quality HR, improvement of IT-based HR quality (education-training), intense mentoring, preparation of PERDA regulations, assistance in financial planning, procurement of facilities and infrastructure, presenting professional trainers from training institutions or partners, working together with financial institutions, building transparent communication patterns, working together with competitors, developing training and assistance activities through continuous education and socialization.